Evolución del discurso de la Unión Europea sobre la seguridad en la región del Ártico - López Tárraga, Ana Belén (2022)
The Arctic was a relevant hotspot during the Cold War. Years later, the global warming derived from climate change is producing transformations that reveal different possibilities to exploit the Arctic’s wealth: natural resources, new trade routes, and tourist activities. This range of opportunities has raised tensions among Russia and United States and European countries. Since 2008, the European Union has been developing its own policy for the Arctic space, being security one of the main challenges that it has to tackle as an international organization. This paper, examines this European Arctic policy through the Conventions Theory to identify the evolution of security issues in the European Union's discourse on the Arctic territory. In order to analyze the situation, we use N-Vivo software to encode the content of fundamental documents published by the EU up to 2021 concerning the Arctic region. The results reflect how security and defense issues have gone from being of secondary importance to being one of the fundamental axes of the current European Arctic policy. El Ártico fue un relevante punto de tensión durante la Guerra Fría. Años después, el calentamiento global está produciendo transformaciones geográficas que dejan al descubierto diferentes posibilidades para la explotación de las riquezas árticas. Este abanico de oportunidades ha elevado las tensiones entre Rusia y Estados Unidos y Europa. Desde 2008, la Unión Europea está desarrollando su propia política para el espacio ártico, siendo la seguridad uno de los principales retos que ha de abordar como organización internacional. Este artículo examina esta política ártica europea a través de la teoría de los órdenes de justificación para identificar la evolución de las cuestiones relativas a la seguridad y la defensa en el discurso de la Unión Europea sobre el territorio ártico. Se ha utilizado el software N-Vivo para codificar el contenido de los documentos fundamentales publicados por la UE hasta 2021 referidos a la región ártica. Los resultados ...